Cell culture propagation of a coronavirus isolated from cows with winter dysentery. - Benfield, D A (1990)
Fecal filtrates from cows with winter dysentery were inoculated into gnotobiotic and conventional calves, and a coronavirus was isolated from calf feces. Cytopathic effects were observed on human rectal tumor cells but not bovine cell cultures. The winter dysentery isolates morphologically and antigenically resembled the Mebus strain of bovine coronavirus.